Karate dancer - Smith, Doris Buchanan (New York : Putnam's, 1987)
Passionate about karate, fourteen-year-old Troy tries to convince his disapproving parents about the true nature of the art and its importance in his life.
6.4
6.4
5-8.
5-8
Keywords: Karate -- Fiction; Parent and child -- Fiction; Karate -- Fiction; Parent and child -- Fiction